The mindful therapist: an interpretive phenomenological analysis of mindfulness meditation and the therapeutic alliance - Gillitt, Tarryn (Rhodes University, Faculty of Humanities, Department of Psychology, 2011)
The aim of this study was to present and understand therapists' experiences of the impact of their mindfulness meditation practice on their role in the therapeutic alliance. The topic emerged in response to extant research recommendations and researcher observations of the compatibility between mindfulness meditation outcomes and the demands on therapists for establishing effective alliances with clients. The study adopted an interpretive phenomenological analysis strategy located within the qualitative paradigm, and thus a small sample of therapists practicing mindfulness meditation were selected and interviewed on their experiences using semi-structured interviewing. Data were analysed for meaning units, which were then interpreted inductively and hermeneutically and categorized into superordinate themes. Three superordinate themes within participants' experiences of how their mindfulness meditation practice impacts upon their role in the alliance were determined, namely: 'self-care'; 'insight into the structure of selfhood'; and 'immediate mindfulness meditation during therapy'. This study found these experiences capacitated participants with compassionate interpersonal affects used for creating secure bonds with clients; skills for accurate empathic understanding; and skills and attitudes for working collaboratively with clients. Should future research confirm these findings, mindfulness meditation may be used as a tool to developed alliance formation abilities for therapists in training. Importantly, findings from this project called for a more comprehensive integration of theoretical positions on the construct of mindfulness meditation.
Keywords: Mindfulness-based cognitive therapy; Meditation -- Therapeutic use; Psychotherapy; Counseling psychology